Using Lotus 1-2-3, release 2.2 - Pitter, Keiko M.; Richard Pitter (Watsonville, Calif. : Mitchell Publishing, Inc., 1990)
A brief supplement on Lotus 2.2. This text may be used as a supplement to an introductory computer course taught in information systems, data processing or continuing education. Three disks are also included with the text.
Lesson 1. Components of IBM Micros and Compatibles -- Lesson 2. The Disk Operating System -- Lesson 3. Some Advanced DOS Features -- Lesson 4. Creating a Simple Spreadsheet -- Lesson 5. Enhancing the Simple Spreadsheet -- Lesson 6. Modifying the Display Format -- Lesson 7. Creating Presentation Graphics -- Lesson 8. Using a Spreadsheet as a Database -- Lesson 9. Using other Data Features -- Lesson 10. Using Built-in Functions -- Lesson 11. Printing Reports -- Lesson 12. Multiple Files -- Lesson 13. Introducing Macros -- Lesson 14.Advanced Macro Commands -- Lesson 15. Add-in Programs.
Includes index.
Keywords: LOTUS 1-2-3 (COMPUTER FILE)